Left behind? The effects of digital gaps on e-learning in rural secondary schools and remote communities across Nigeria during the COVID19 pandemic - Gideon Seun Olanrewaju (Elsevier, 2021)
The COVID19 pandemic has contributed to a digital economy by emphasising the importance of digital infrastructure while exposing the digital gaps between countries and communities. For example, during the period of COVID19, schools were closed with no option of online learning due to a deficit of infrastructure around educational technologies. Inequalities in digital access have impeded educational gains made towards achieving the Sustainable Development Goals (SDGs). Though significant studies have been carried out on digital learning, there is currently a dearth of knowledge on students' digital gaps and needs in remote communities in Nigeria. To this end, this research study explored the digital gaps and needs of rural secondary schools in remote communities and its implications on e-learning across 6 Nigerian states, namely Kwara, Ekiti, Ebonyi, Bayelsa, Adamawa, and Kano during the COVID19 era. The study adopted a concurrent embedded mixed method design approach to collect data from rural secondary schools from 6 Nigerian states. Findings from the study identified a lack of ICT strategies and policies in Nigeria, socioeconomic status, poor internet connectivity, electricity, and a high poverty level as the primary drivers of digital gaps in remote communities. Therefore, addressing the digital gaps among students in remote parts of Nigeria will be crucial to achieving the targets of SDGs, particularly SDG 4: Ensure inclusive and equitable quality education and promote lifelong learning opportunities for all by 2030.